2020
DOI: 10.1007/s00787-020-01515-6
|View full text |Cite
|
Sign up to set email alerts
|

Why do depression, conduct, and hyperactivity symptoms co-occur across adolescence? The role of stable and dynamic genetic and environmental influences

Abstract: Depression, conduct, and hyperactivity symptoms are chronic and frequently co-occur in adolescence. Common genetic and environmental vulnerability to these conditions have previously been demonstrated, however, the manner in which common versus disorder-specific etiological influences operate across development and maintain symptom co-occurrence is unclear. Thus, the current study investigated the role of common genetic and environmental influences in the comorbidity of depression, conduct, and hyperactivity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 84 publications
1
12
0
Order By: Relevance
“…However, the findings should be interpreted in the context of some limitations. First, unmeasured factors including genetic vulnerability may account for observed associations [73][74][75], and other forms of residual confounding cannot be ruled out. Second, the study was not without attrition, yet the study retained around 90 percent of the original cohort, with a relatively small proportion of missingness across the follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…However, the findings should be interpreted in the context of some limitations. First, unmeasured factors including genetic vulnerability may account for observed associations [73][74][75], and other forms of residual confounding cannot be ruled out. Second, the study was not without attrition, yet the study retained around 90 percent of the original cohort, with a relatively small proportion of missingness across the follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…In a study with adolescents, common genetic features and liability contributed to the co-occurrence of depression, conduct, and hyperactivity symptoms [29]. Based on twin studies, there are common grounds to say that comorbidities have genetic features [29,32]. Children with externalizing symptoms are more vulnerable to harmful effects related to stressful events.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding structure of psychopathology findings, similar results to those reported by Lahey et al (2011) have been found in more recent studies conducted with adolescents. These studies suggest a stable genetic factor to represent common liability, and to account for the co-occurrence between different symptoms (Waszczuk et al, 2020). Moreover, this general factor and specific externalizing and internalizing dimensions characterize youth psychopathology at both the phenotypic and etiologic levels (Waldman et al, 2016).…”
Section: Genetic and Environmental Etiological Influencesmentioning
confidence: 94%
“…Behavior genetics has supported the structure of psychopathology in adults (Hicks et al, 2004;Kendler et al, 2003;Rosenström et al, 2019), and youths (Cosgrove et al, 2011;Gjone & Stevenson, 1997;Lahey et al, 2011;Marceau & Neiderhiser, 2020;Waldman et al, 2016;Waszczuk et al, 2020;Young et al, 2000). For instance, the findings of Young et al (2000) indicated that a variety of adolescent problem behaviors share a common underlying genetic risk.…”
Section: Genetic and Environmental Etiological Influencesmentioning
confidence: 99%
See 1 more Smart Citation